Standard specification for nickel-copper alloy rod, bar, and wire
This specification covers nickel-copper alloys UNS N04400 and N04405* in the form of hot-worked, and coldworked rod and bar, and cold-worked wire. The values stated in inch-pound units are to be regarded as the standard. The values given in parentheses are for information only.